Case Report: Acute Fulminant Cerebral Edema With Perivascular Abnormalities Related to Kawasaki Disease - Maeda, Kenichi; Chong, Pin Fee; Akamine, Satoshi; Yamashita, Fumiya; Morooka, Yuya; Mori, Harushi; Lee, Sooyoung; Mizuno, Yumi; Kira, Ryutaro (Frontiers in Pediatrics, 2021)
Introduction: Kawasaki syndrome (KD) is an acute systemic vasculitis in children, but 0.4% of patients with KD exhibit central nervous system involvement. Acute encephalitis and encephalopathy accompanied with KD have been reported to be mostly self-limiting complications. Case presentation: A 2-year-old girl developed recurrent vomiting, a cluster of generalized seizures, and decreased consciousness on day 12 after the onset of KD. Magnetic resonance imaging (MRI) T2-weighted images on day 13 showed high signal intensities in bilaterally symmetrical and subcortical white matter and thalamus, and linear radial hyperintensities parallel to the cerebral vessels of the periventricular white matter. Diffuse white matter hyperintensity on the apparent diffusion coefficient map suggested vasogenic edema. Subsequently, lethal cerebral edema rapidly progressed in 8 hrs after the MRI examination. Conclusion: To our knowledge, acute fulminant cerebral edema in patients with KD has not been previously reported. We should be aware of the possibility of severe encephalitis related to KD. Furthermore, diffuse white matter vasogenic edema with perivascular abnormalities on MRI may be an alerm, potentially leading to fatal cerebral edema.